Tax Competition, Capital Mobility and Public Good Provision Within a Trading Block - Costas Hadjiyiannis; Panos Hatzipanayotou; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2001)
We construct a general equilibrium model of a two-country trading block where governments through tax policies attract mobile capital, and provide an imported public consumption good. At Nash equilibrium, when the public good is under-provided, (i) a country with a large GDP, has a large Nash equilibrium income tax rate, (ii) if initially the existing foreign capital in the country is zero or small, then the country with a large population or high individual marginal willingness to pay for the public good has a large Nash equilibrium income tax rate. When the two countries act cooperatively, then for each country, the cooperative optimal income tax rate is positive, and if they are identical then the cooperative income tax rate is greater than the Nash. When the two countries are different, then it is possible that the cooperative income tax rate is less than the Nash.
Keywords: 330; Nash and cooperative income taxes; capital mobility; public goods